A global bibliometric analysis on Kawasaki disease research over the last 5 years (2017–2021) - Tan, Weifu; Jing, Liao; Wang, Yunxiao; Li, Wei (Frontiers in Public Health, 2023)
Abstract Background: Kawasaki disease (KD) is a systemic vasculitis of unknown etiology that mainly affects children. We aim to conduct a bibliometric analysis to explore the latest research hotspots and trends of KD. Method: By using the keywords "Kawasaki disease", "Kawasaki syndrome" and "Mucocutaneous Lymph Node Syndrome", the Web of Science (WOS) and Scopus databases were searched for publications related to KD from 2017 to 2021. Author, country and journal submissions were classified and evaluated using Biblioshiny software (using R language). VOSviewer (version 1.6.18) was used to visualize the relevant network relationships. Result: According to the search strategy, 5848 and 6804 KD studies were published in WOS and Scopus, respectively. The results showed an overall increasing trend in the number of publications and citations during the study period. The three most influential institutions in the WOS were St. Marianna University, Kawasaki Medical School and The University of Tokyo in Japan, while in Scopus, Harvard Medical School, University of California and Tehran University of Medical Sciences were the most influential institutions. The most influential authors of the two databases are Goodman SG, Kazunori Kataoka, and Takeshi Kimura of the WOS and Marx Nikolau and Wang Y, Burns JC, and Newburger JW of the Scopus, respectively. And Scientific Reports and Frontiers in Pediatrics were the most critical journals. The most cited documents were the WOS document by McCrindle BW et al. and the Scopus document by Benjamin EJ et al. published in 2017, while the keywords in the last few years were focused on "COVID-19", "multisystem inflammatory syndrome" and "pandemic". Conclusion: This bibliometric analysis summarizes for the first time the research progress in KD (2017-2021), providing a qualitative and quantitative assessment of the bibliometric information on KD research. In this field, researchers mainly from Japan and USA are dominant, followed by China. It is recommended to pay close attention to the latest hot spots, such as "COVID-19" and "multisystem inflammatory syndrome". These results provide a more intuitive and convenient way for researchers to obtain the latest information on KD research.